Post-mortem examinations of New Zealand birds. 2. Long-tailed cuckoos (Eudynamys taitensis, Aves: Cuculinae)*. Issue 4 (2nd October 2018) - Gill, B. J.; Zhu, Amy; Patel, Selina
ABSTRACT: Little is known about the biology of long-tailed cuckoos ( Eudynamys taitensis ). In this study, 79 dead cuckoos, mostly from the wider Auckland region, New Zealand, were examined and dissected to shed light on the sex ratio, morphology, breeding season and diet. There were no statistically significant sexual differences in the means for weight or body measurements. However, immature birds had significantly shorter bill, wing and tail lengths than adults. In adults, gonads were enlarged (for breeding) from October to January, while all cuckoos identified (from plumage) as immatures had small gonads. Of 888 food items identified from 62 gizzards, 94% were insects. The main foods were cicadas and shield-bugs (Hemiptera, 48% of food items), stick-insects (Phasmatodea, 19%) and wētās and katydids (Orthoptera, 13%). Small vertebrates (lizards and birds' eggs and nestlings) were a minor dietary element (1% of food items; 13% of stomachs). Cicadas, stick-insects and praying mantids (large insects abundant in late summer) made up 57% of the immature diet; in adults these three categories made up just 13% of food items. Immatures leave New Zealand on migration several months after adults, and this delay in late summer and autumn coincides with an opportunity to exploit a seasonal abundance of large insects.